KEMISKINAN DAN KESENJANGAN PENDAPATAN - Insani, Afrial; Firma Nanda; Septiyani Nur Rohanah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Poverty and income inequality are interconnected socio-economic issues and constitute major challenges in national development. This study aims to analyze the factors influencing poverty and income inequality in Indonesia and to identify the relationship between these two phenomena. The data utilized were obtained from the National Socio-Economic Survey (Susenas) and the Central Bureau of Statistics (BPS) for the year 2023. The analytical methods applied include multiple linear regression to determine the effect of economic variables, education, and access to public services on poverty levels, and the Gini index to measure income inequality. The results indicate that education level, access to formal employment, and distribution of public services significantly affect poverty reduction. Furthermore, a positive correlation exists between income inequality and poverty levels, suggesting that economic disparity exacerbates the social conditions of the poor. These findings underscore the importance of inclusive policies focusing on equitable economic opportunities and improving human capital quality.